A survey on COVID-19 vaccine acceptance and concern among Malaysians - Syed Alwi, Syed Abdul Rahman; Rafidah, Elias; Zurraini, Arabi; Juslina, Omar; Imam, Bux Brohi; Sabrina, Lukas (BioMed Central Ltd, 2021)
Background Vaccination is an effective way to curtail the burden of COVID-19 in which success depends on a high acceptance of the vaccine. However, addressing concerns among vaccine-hesitant individuals is essential to avoid failure of the immunisation programme. This study sought to assess the concerns and acceptance rates regarding the COVID-19 vaccine among Malaysians.